Similar but Different: Psychological and Psychopathological Features of Primary and Secondary Hikikomori - Frankova, Iryna (Frontiers in Psychiatry, 2019)
Recently, there has been an increase in reports of hikikomori around the globe, and Ukraine is not an exception. The development of hikikomori is often spurred by a history of aversive or traumatic childhood experience, e.g. dysfunctions between parents or between a parent and a child (ambivalent attachment) and difficulties at school (peer rejection). Previously described models of hikikomori development mostly were based on research of mixed cohorts of patients (with and without psychiatric comorbidity). To test, whether there was a difference in psychological and psychopathological features between primary hikikomori (HG1, n=13) and secondary hikikomori (HG2, n=22) comorbid with neurotic, somatoform and stress-related disorders (F40-48, ICD-10), they were compared with each other and with a healthy control group (CG, n=28). Sociodemographic data, alexithymia, traumatic life events, hostility, quality of life, and personality traits were evaluated. No relevant or statistically significant differences have been found between primary and secondary hikikomori, except for greater hostility in the latter. When compared with the healthy control group, the primary hikikomori were found to have higher frequency of alexithymia, lifespan traumatic events (7±3.6), as well as higher levels of resentment and verbal hostility, and a bigger aggression index. In secondary hikikomori, higher irritability and resentment have been observed, with more dysthymia, excitability and anxiety, and although the frequency of psychological traumas was lower (5.5±4), it was still significant. Primary and secondary hikikomori had largely similar characteristics in the Ukrainian sample studied, but more studies with larger samples are needed to validate generalizability of the findings.